Number 22 (October 1990) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1991)
(October 1990) - Fishes of Springs and Spring-fed creeks of Calhoun County Alabama. By D.R. Sizemore and W.M. Howell, 6 pp. Pebble-nests of Four Semotilus Species. By W.F. Maurakis, et al., 7 pp. Evidence for a Genetically Unique Walleye Population in the Upper Tombigbee River System of Northeastern Mississippi. By B.R. Murphy, 3 pp.
Keywords: fishes; calhoun county; pebble-nests; smotilus; walleye; tombigbee river